2009
DOI: 10.1177/0748730408329109
|View full text |Cite
|
Sign up to set email alerts
|

RNA Interference of the Period Gene Affects the Rhythm of Sperm Release in Moths

Abstract: The period (per) gene is 1 of the core elements of the circadian clock mechanism in animals from insects to mammals. In clock cells of Drosophila melanogaster, per mRNA and PER protein oscillate in daily cycles. Consistent with the molecular clock model, PER moves to cell nuclei and acts as a repressor of positive clock elements. Homologs of per are known in many insects; however, specific roles of per in generating output rhythms are not known for most species. The aim of this article was to determine whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 35 publications
3
35
0
Order By: Relevance
“…Reduced per mRNA levels affected the egg hatching rhythm in the silk moth Bombyx mori (Sandrelli et al, 2007) and inhibited the locomotor activity rhythm and rhythmic electrical activity in the optic lobes in crickets Gryllus bimaculatus (Moriyama et al, 2008). Furthermore, we have recently shown that per RNAi inhibited sperm release rhythm in the moth S. littoralis (Kotwica et al, 2009a).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Reduced per mRNA levels affected the egg hatching rhythm in the silk moth Bombyx mori (Sandrelli et al, 2007) and inhibited the locomotor activity rhythm and rhythmic electrical activity in the optic lobes in crickets Gryllus bimaculatus (Moriyama et al, 2008). Furthermore, we have recently shown that per RNAi inhibited sperm release rhythm in the moth S. littoralis (Kotwica et al, 2009a).…”
Section: Introductionmentioning
confidence: 95%
“…Another difference is that PER and TIM, which translocate to cell nuclei in the fruit fly, are predominantly cytoplasmic in neurons of other insects. However, PER was detected in cell nuclei in peripheral organs, such as larval midgut of Antheraea pernyi (Sauman and Reppert, 1998), epithelial cells in the antenna of Manduca sexta (Schuckel et al, 2007) and vas deferens epithelium in the Cydia pomonella (Gvakharia et al, 2000) and Spodoptera littoralis (Kotwica et al, 2009a).…”
Section: Introductionmentioning
confidence: 98%
“…Giebultowicz, 2004;Howlader and Sharma, 2006;Sellix and Menaker, 2010;Yoshikawa et al, 2009). In the fruit fly and moths, the circadian clock genes per and tim have been found to be directly connected with male reproductive capacity (Beaver et al, 2002;Kotwica et al, 2009). Previously, the effect of a knockdown of these genes in the desert locust has been reported for female S. gregaria which was comparable to the effect in female per and tim loss-of-function mutant fruit flies (Beaver et al, 2003).…”
Section: Discussionmentioning
confidence: 94%
“…RNAi experiments in Spodoptera littoralis indicated that per has a role in the regulation of sperm release in the male reproductive system (Kotwica et al, 2009). Moreover, sperm that is released from the testes undergoes further maturation in the male reproductive tract and accessory glands.…”
Section: Per and Tim Knockdown Affects Male Reproductive Capacitymentioning
confidence: 99%
See 1 more Smart Citation